(untitled) - Blake, Nicholas; Nicholas Blake; Raza Husain (Oxford,New York, 2003)
This book addresses the material details of the Human Rights Act 1998 in the UK and examines the very different new scheme of immigration control mandated by the Immigration and Asylum Act 1999. The authors then analyze the impact of the Human Rights Act 1998
Keywords: Emigration and immigration law; Human rights; Asylum; Right of